Effect of epibrasslnolide on the ultrastructure of epidermous cell in hypocotyl segments of mung bean seedings - CHEN Li-ping; WANG Bing-liang; CHEN Ji-chu; ZHAO Yu-ju (浙江大学学报. 农业与生命科学版)
The effects of epibrassinolide on ultrastructure of epidermous cell in hypocotyl segments of mung bean seedlings were studied. Hypocotyl segments treated with epibrassinolide (1 mg/L) maintained the integrity of ultrastructure of cell, and retarded the senescence, whereas the various organelles of the controls deteriorated after 5 days in vitro. The relationship between the effect of epibrassinolide in maintaining the integrity of ultrastructure of cell and retarding senescence was discussed.